Entrepreneurship : theory, process, practice - Kuratko, Donald F. (Australia : Cengage Learning Asia Pte Ltd, 2014)
Entrepreneurship is the most powerful economic force known to humankind! The "entrepreneurial revolution" that captured our imagination during the 1990s has now permeated every aspect of business thinking and planning.
The Entrepreneurial mind-set in the twenty-first century -- Initiating entrepreneurial ventures -- Developing the entrepreneurial plan -- Growth strategies for entrepreneurial ventures
Includes index.
Keywords: ENTREPRENEURSHIP